From Freud to Kafka : the paradoxical foundation of the life-and-death instinct - Réfabert, Philippe (Karnac Books, 2014)
This book takes the reader on a captivating journey leading from an erroneous founding assumption inherited from Freud, to the proposal of a principle better suited to allowing the psychoanalyst to accompany the patient out of his impasse. The founding assumption of the book, already questioned by many analysts among whom Sandor Ferenczi figures as a brilliant forerunner, was the author's starting point in re-examining the basic precepts of psychoanalysis. Reading Kafka made the author conclude that this masterful storyteller describes borderline situations, so familiar to him, better than anyone. An avid reader of Freud, Kafka suggests that the human capacity to bear a paradoxical position between life and death is not given to the child naturally, at birth. Kafka seems to say that giving life is easy, but that giving it the necessary support in the form of the trace of death is more problematic. Moreover, when the child is deprived of this trace, he faces the void and, in a panic, must use emergency measures to construct a substitute for the necessary trace of death; and he can only do so by sacrificing his sexuality, his ability to feel, his initiative or his judgement. When the conditions necessary for primal repression are not provided to the child by others, he creates them himself at great cost. What he gives himself is not life, but life-death, and he pays the price for doing so. When primal repression is destroyed - something which can happen at any age - we speak of "soul murder". At the very instant when it occurs, a new Subject comes into existence, a Subject who pushes back the threat of destruction. The new Subject constructs otherness out of an object or out of a part of himself, a part he sacrifices in order to recover the primal repression destroyed by the trauma. This book will interest not only psychotherapists, psychoanalysts, philosophers and students of literature, but also a wide range of readers with a passion for the complexities of the human soul